PENINGKATAN KERJA SAMA DAN EMPATI SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF INSIDE OUTSIDE CIRCLE PADA SISWA KELAS V MADRASAH IBTIDAIYAH ISTANA BERKAH ABADI (IBA) KOTA JAMBI - Humairah, Nadia; Sari, Sri Yulia; Al Faris, Salman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low levels of cooperation and empathy among fifth-grade students at Istana Berkah Abadi (IBA) Elementary School in Jambi City during the learning process. The study aimed to improve student cooperation and empathy through the implementation of the Inside Outside Circle cooperative learning model. The research design used was Classroom Action Research (PTK), conducted in two cycles. The data collection techniques used were observation and documentation. The research instruments used were teacher activity observation sheets, student activity observation sheets, cooperation observationsheets, and student empathy observation sheets. Based on the results of data processing from observations of student cooperation involving 22 respondents, the results were: an average of 64.3% in Cycle I and 84.15% in Cycle II. The results of the student empathy observations were obtained in Cycle I, with an average of 67.8% in Cycle II, and an average of 86.8% in Cycle III. These results indicate that the implementation of the Inside Outside Circle learning model can improve cooperation and empathy among fifth-grade students at Istana Berkah Abadi (IBA) Elementary School in Jambi City.